PERTUMBUHAN DAN PRODUKSI BIBIT TEBU G3 KULTUR JARINGAN VARIETAS PS 862 PADA PERLAKUAN JARAK TANAM DAN PUPUK KANDANG / The Production of Tissue Culture Cane Seed G3 PS862 Variety on Plant Spacing and Cow Manure Application - Sumanto Sumanto (Pusat Penelitian dan Pengembangan Perkebunan, 2016)
Methods for increasing cane seed stock i.e by using hormones, tissue culture, fertilization, plant spacing, seed types, and organic fertilizer were used. Plant spacing is one factor to obtain optimal growth and plant production. Organic fertilizer can increase soil fertility, chemical fertilizer efficiency, and soil organic matter. Research conducted at the Experimental Station Sukamulya, Sukabumi, on Latosol. The aims of the experiment were to study the influence of plant spacing and manure on production G3 cane seed from tissue culture. Randomized complete block design were used, consisted of two factors, first factor was plant spacing, consisted of five levels. The second factor was manure doses, consisted of four levels. The parameters observed were number of stalks, number of leaves, stalk weight and diameter, number of bud and sprouted bud per clump. Production cane seed are affected by plant spacing. The highest number of stalks (4,2 stalks/clump), number of bud (57,60 buds/clum), and number of sprouted bud/clump (39,71 buds/clump) obtained by plant spacing of 110 cm x 40 cm. As well as manure application significantly affected production of seed cane, application of 9 tonnes/ha provides the highest number of sprouted bud/clump (41,34 sprouted buds/clump) gave significantly from the other treatments. Plant spacing and manure provide significantly interaction the content of N and P content in leaves. Application of manure 6 tonnes/ha at plant spacing of 120 cm x 40 cm provides the highest content of N and P in leaves, 1.47% and 0.16% respectively. The highest K content obtained at plant spacing of 100 cm x 40 cm by application of manure 6 tonnes/ha.